2014
DOI: 10.1016/j.cub.2014.09.081
|View full text |Cite
|
Sign up to set email alerts
|

Yorkie and Scalloped Signaling Regulates Notch-Dependent Lineage Specification during Drosophila Hematopoiesis

Abstract: Summary Cellular microenvironments established by the spatial and temporal expression of specific signaling molecules are critical for both the maintenance and lineage-specific differentiation of progenitor cells. In Drosophila, a population of hematopoietic progenitors, or prohemocytes, within the larval lymph gland [1] gives rise to three mature cell types: plasmatocytes, lamellocytes, and crystal cells. Removal of the secreted signaling molecules Hedgehog [2] and PVF1 [3] from the Posterior Signaling Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 21 publications
5
57
0
Order By: Relevance
“…Rather only the crystal cells were labeled by both GFP and RFP (also seen by Hnt). This crystal cell specific restriction of GFP and RFP expression can be explained by requirement of Notch for maturation, maintenance and survival of this cell type (Lebestky et al, 2003; Mukherjee et al, 2011; Terriente-Felix et al, 2013; Duvic et al, 2002; Ferguson and Martinez-Agosto, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Rather only the crystal cells were labeled by both GFP and RFP (also seen by Hnt). This crystal cell specific restriction of GFP and RFP expression can be explained by requirement of Notch for maturation, maintenance and survival of this cell type (Lebestky et al, 2003; Mukherjee et al, 2011; Terriente-Felix et al, 2013; Duvic et al, 2002; Ferguson and Martinez-Agosto, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…This cross-talk is strikingly cell-type and context specific, because even within one organism (e.g. Drosophila melanogaster ), Notch activates YAP in the lymph gland, inhibits Hippo signaling in the wing disc, and Notch-Hippo have an inverse relationship in oocytes (3234). Crosstalk between these two pathways in the pediatric cancer eRMS has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated the importance of the Hippo pathway in fly hematopoiesis. 25,26 It was also reported that key proteins of the Hippo pathway are expressed in mantle cell lymphoma. 27 Furthermore YAP, a key component of the Hippo pathway, is highly expressed in stem cells and decreases progressively during differentiation.…”
Section: Discussionmentioning
confidence: 99%